Epitaf Jurija Ravbarja - Oter Gorenčič, Mija (Zbornik za umetnostno zgodovino (Nova vrsta), 2021)
The contribution at hand presents the discovery of the identity of the person to whom the epitaph on the pier between the main nave and the southern nave under the choir loft of the Cistercian church in Stična was dedicated. The fresco is considered the only sign of the Renaissance in the Slovenian hinterlands in the early 1480s. The article demonstrates that the fresco was painted for Georg Rauber. The author determines that the painted fresco lunette originally contained several coats of arms, of which only the coat of arms of the Kingdom of Hungary has been preserved. She interprets the coats of arms as an expression of loyality to Emperor Frederick III, whose archducal seal included the coat of arms of the Kingdom of Hungary and the coats of arms of Austria, Carinthia, and Windic March to the left of his portrait.
Keywords: 15. st.; 15th cent.; cerkveno slikarstvo; church painting; epitaphs; Georg Rauber; Jurij Ravbar; nagrobne freske; Samostan Stična (Slovenija)